A three-dimensional finite element analysis to evaluate stress distribution tooth in tooth implant-supported prosthesis with variations in non-rigid connector design and location - K Sumathi Nitin; T V Padmanabhan; V Anand Kumar; N Parthasarathi; M Uma Maheswari; S Madhan Kumar (Wolters Kluwer Medknow Publications, 2018)
Background: The physiologically mobile natural tooth and rigidly fixed dental implant causes different distribution of stress when connected in prosthesis and nonrigid connector compensates this. Understanding of biomechanical behavior is necessary for an adequate choice and construction of this type of rehabilitation. However, there has been insufficient research focusing on different location and type of the nonrigid connector related with the prognosis of both implant and the tooth. Aim of the Study: The purpose of this finite element (FE) analysis was to evaluate the stress distribution around bone, implant, and tooth in tooth implant fixed prosthesis under static load with variations in design and location of nonrigid connectors under simulated functional loads. Materials and Method: Three, 3-dimensional FE models connecting tooth and implant were constructed with different location and type of nonrigid connector. Simulated occlusal load was applied on the restorations and stresses developed in the supporting structures were monitored. Results: The highest stresses were found around the implant in model with nonrigid connector placed between the tooth and implant and model with modified nonrigid connector. On the other hand, less stress was noted around the implant where nonrigid connector was placed between the implant and pontic. Conclusion: It is advisable to place the nonrigid connector between the implant and the pontic to protect the implant from torque effects in a tooth implant fixed prosthesis.